Predictors of prolonged hospitalization among children aged 2–59 months with severe community-acquired pneumonia in public hospitals of Benishangul-Gumuz Region, Ethiopia: a multicenter retrospective follow-up study - Dinku, Habtamu; Amare, Dessalegn; Mulatu, Sileshi; Abate, Melsew Dagne (Frontiers in Pediatrics, 2023)
Background: Pneumonia is a leading cause of morbidity and mortality among children under five years of age in Ethiopia. Prolonged hospitalization of severe community acquired pneumonia is a significant problem in resource limited counties. This study seeks to provide insights that can help improve the management and outcomes of severe community acquired pneumonia which is particularly important in the context of Benishangul Gumuz Region, Ethiopia, where access to quality healthcare services is limited, and childhood pneumonia is a significant health challenge.Objective: This study aimed to determine predictors of prolonged hospitalization among 2-59 months of children admitted with severe community acquired pneumonia in Benishangul Gumuz Region public hospitals, Ethiopia.A retrospective follow-up study design was conducted among randomly selected samples of 526 children. Data were entered into EPI data version 4.6 and analyzed using STATA version 14.0. Cox proportional hazard regression model was fitted to identify the independent predictors of prolonged hospitalization, and variables having a p-value < 0.05 in the multivariable model were considered statistically significant.Results: -The median hospital stay was 5 days (IQR 2 -8 = 6). About 149(28.93%) had prolonged hospitalization (>5 days) and the recovery rate from severe community acquired pneumonia was 19.69 per 100 person-day observations. Having facility referral sources (0.79, 95% CI 0.63-0.98), Wasting (0.64, 95%CI 0.44-.94), anemia (0.65, 95% 0.46-0.90), no identified hemoglobin level (0.53, 95%CI 0.41-0.70), no identified blood film (0.65, 95% CI 0.53-0.80), no chest x ray investigation(0.81, 95% CI 0.65-0.99), pulmonary effusion (0.31, 95% CI 0.15-0.66) and late presenters to hospital (0.67, 95% CI 0.53-0.84) at admission were significant predictors of prolonged hospitalization.The median hospital length of stay was delayed compared to other studies. Wasting, late presenting to hospital, pulmonary effusion, anemia, absence of investigations of hemoglobin level, chest x-ray and blood film at admission time were factors that significantly prolonged the hospitalization time. Hence, attention should give to prevention of malnutrition and anemia in children, increasing the community early health seeking behavior. Attention should be given to complications like pleural effusion and investigations like chest x-ray, hemoglobin level and blood films should be performed at admission of the child.